O interdyscyplinarności komparatystyki - Płaszczewska, Olga (Studia Europaea Gnesnensia, 2013)
The purpose of the text is to discuss some basic meanings of interdisciplinarity in the area of comparative literature (that concerns both, analysed problems and the methodology applied). A special attention is paid to the field of so called „correspondence of arts” and to one of the principal rules of the discipline, consisting in considering literature a constant and obligatory element in the comparative reflection.